Oxford Medicine Online 2018
DOI: 10.1093/med/9780199592548.003.0149_update_001
|View full text |Cite
|
Sign up to set email alerts
|

The patient with diabetes mellitus

Abstract: About one third of patients with type 1 diabetes develop diabetic nephropathy long-term (usually not before at least 10 years of diabetes), though this proportion is falling as standards of care have risen. Nephropathy is strongly associated with other microvascular complications of diabetes, so that some degree of retinopathy is to be expected, and evidence of neuropathy is common. Patients with type 2 diabetes are equally susceptible, but this is an older group in which vascular disease and other pathologies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Diabetic nephropathy is currently the leading cause of ESRD in the western world. Consequently, diabetes is a principal cause for patients requiring renal replacement therapy, with diabetic patients contributing to approximately 45% of the individuals on renal replacement therapy worldwide [15].…”
Section: Classification Of Diabetic Nephropathymentioning
confidence: 99%
See 3 more Smart Citations
“…Diabetic nephropathy is currently the leading cause of ESRD in the western world. Consequently, diabetes is a principal cause for patients requiring renal replacement therapy, with diabetic patients contributing to approximately 45% of the individuals on renal replacement therapy worldwide [15].…”
Section: Classification Of Diabetic Nephropathymentioning
confidence: 99%
“…Experimental models of diabetes have demonstrated that elevated circulating levels of glucose and free fatty acids can both be potent activators of NADPH oxidase [76][77][78][79][80][81]. Further metabolicmediated increased activation of the RAAS [15] has been recognised as one of the major activators of NADPH oxidase and oxidant species formation [82,83].…”
Section: Oxidative Stress In the Glomerulusmentioning
confidence: 99%
See 2 more Smart Citations
“…In patient with diabetes mellitus and/or hypertension, chronic perturbations such as hyperglycaemia, dyslipidaemias and haemodynamic insults (elevated systemic‐hypertension and intraglomerular pressure) result in ER stress 49,50 and are important factors driving renal decline progression towards CKD and ESRD 51,52 …”
Section: Er Stress and Upr In Kidney Diseasementioning
confidence: 99%